Navigating the ‘Ideology of Eros’ in the Politics of Recognition: Love and the Ethic of Non-Recognition - Hurst, Andrea (Theoria (Pietermaritzburg), 2024)
This article discusses Charles Taylor's analysis of the ‘politics of recognition’, which reveals that the major versions of the latter share an ideological conception of Eros as a binding, unifying force. Such striving for oneness is seen as key to forming harmonious, just communities and nations, and ultimately global cohesion. I refer to this as the ‘ideology of Eros’. However, Taylor highlights an ironically divisive opposition concerning how to realise such oneness, based on incompatible foundational principles: ‘sameness’ and ‘difference’. Instead of a choice, Taylor opts for the demanding political task of ongoing negotiation between them. I augment Taylor's analysis by re-evaluating the figure of ‘non-recognition’ arising from Lacan's critique of the ‘ideology of Eros’, which is centred on Socrates’ encounter with Alcibiades in Plato's Symposium and to which he adds his notion of genuine love, which affirms an ethic of healthy ‘non-recognition’. I argue that this ethic supports the difficult political task that Taylor rightly calls for.